2019
DOI: 10.1158/1078-0432.ccr-18-3241
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Subtype Not Immune Response Drives Outcomes in Endometrial Carcinoma

Abstract: Purpose: Tumors with high mutation load are thought to engender stronger immune responses, which in turn promote prolonged patient survival. To investigate this, we assessed tumor-infiltrating lymphocytes (TILs) and immunosuppressive factors across the 4 molecular subtypes of endometrial cancer, which have characteristic mutation rates ranging from low to ultra-high.Experimental Design: A total of 460 endometrial cancers were stratified by ProMisE (Proactive Molecular Risk Classifier in Endometrial cancer) int… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
94
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 107 publications
(112 citation statements)
references
References 68 publications
(100 reference statements)
10
94
1
Order By: Relevance
“…While previous studies have shown the strong prognostic value of the molecular EC classification [11,16], and of the density of tumor-infiltrating lymphocytes in EC [19,20], to our knowledge our study is one of only two to examine the combination of these factors. The other study, by Talhouk and colleagues [23], reported no prognostic effect of intraepithelial CD3 + CD8 + cells in multivariable analysis which included the molecular EC classification, although a tendency to improved survival was observed. The discordance with our results is currently unexplained, but may relate to the methodology used for immune cell localization, statistical analysis, or the smaller, non-trial population of mixed histotypes and stages used in their study.…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…While previous studies have shown the strong prognostic value of the molecular EC classification [11,16], and of the density of tumor-infiltrating lymphocytes in EC [19,20], to our knowledge our study is one of only two to examine the combination of these factors. The other study, by Talhouk and colleagues [23], reported no prognostic effect of intraepithelial CD3 + CD8 + cells in multivariable analysis which included the molecular EC classification, although a tendency to improved survival was observed. The discordance with our results is currently unexplained, but may relate to the methodology used for immune cell localization, statistical analysis, or the smaller, non-trial population of mixed histotypes and stages used in their study.…”
Section: Discussionmentioning
confidence: 91%
“…While the potential clinical utility of both the molecular EC classification and quantification of the antitumor immune response appear considerable, the variable prognosis of molecular EC subgroups may be explained by a marked variation in intratumoral T-cell infiltrate between them [21,22], and it is unclear whether these genomic and immune biomarkers confer independent prognostic value. An analysis of an EC cohort of mixed stages and histotypes demonstrated that while application of the molecular classification improves upon the prognostic value provided by clinicopathological variables, the additional analysis of Tcell infiltrate conferred no further benefit [23]. Here, we examined this in a more homogenous population of stage I endometrioid ECs from two large randomized clinical trials.…”
Section: Introductionmentioning
confidence: 99%
“…POLE EDMs in ECs not described previously in the TCGA classification. The presence of a pathogenic POLE EDM is causal for ultramutated EC, a subtype associated with enhanced immune response [2,42] and excellent clinical outcome [6,7,13]. De-escalating adjuvant treatment in these patients is currently under investigation in the randomised PORTEC4a trial.…”
Section: Estimation Of Pathogenicity Of Somatic Pole Mutations In Thementioning
confidence: 99%
“…Despite treatment, such as surgical resection, chemotherapy, and/or radiotherapy, the survival rate of EC is low due to its propensity to proliferate and metastasize. Immunotherapy is effective for EC, and immune cells, which infiltrate in the tumour microenvironment, play important roles in tumour progression and metastasis [2].…”
Section: Introductionmentioning
confidence: 99%